Successful angioplasty during pregnancy for renal artery stenosis. Issue 3 (28th January 2016) - Margueritte, François; Velasco, Stephane; Pourrat, Olivier; Pierre, Fabrice
Abstract: Renal artery stenosis can be diagnosed during pregnancy and treated at the same time. A 30‐year‐old woman had a sudden, severe but asymptomatic hypertensive crisis at 21 weeks of gestation. The diagnosis of renal artery stenosis suspected on Doppler ultrasonography was confirmed and treated by renal angioplasty, which reduced her blood pressure. At 27 weeks of gestation, her blood pressure increased again, associated with significant proteinuria, suggesting pre‐eclampsia. A cesarean section was performed giving birth to a healthy 940‐g child. Renal artery stenosis should be considered when sudden and early‐onset hypertension appears during pregnancy.